Association of perceived partner non-monogamy with prevalent and incident sexual concurrency. (16th November 2015) - Sanchez, Diana M; Schoenbach, Victor J; Harvey, S Marie; Warren, Jocelyn T; Adimora, Adaora A; Poole, Charles; Leone, Peter A; Agnew, Christopher R
Abstract : Objectives: Concurrency is suggested as an important factor in sexually transmitted infection transmission and acquisition, though little is known regarding factors that may predict concurrency initiation. We examined the association between perception of a partner's non-monogamy (PPNM) and simultaneous or subsequent concurrency among at-risk heterosexual young adults in the Los Angeles area. Methods: We used Poisson regression models to estimate the relationship between PPNM and incident concurrency among 536 participants participating in a cohort study, interviewed at 4-month periods during 1 year. Concurrency was defined as an overlap in reported sexual partnership dates; PPNM was defined as believing a partner was also having sex with someone else. Results: Participants (51% female; 30% non-Hispanic white, 28% non-Hispanic black, 27% Hispanic/Latino) had a mean age of 23 years and lifetime median of nine sex partners. At each interview (baseline, 4-month, 8-month and 12-month), 4-month concurrency prevalence was, respectively, 38.8%, 27.4%, 23.1% and 24.5%. Four-month concurrency incidence at 4, 8 and 12 months was 8.5%, 10.6% and 17.8%, respectively. Participants with recent PPNM were more likely to initiate concurrency (crude 4-month RR=4.6; 95% CI 3.0, 7.0; adjusted 4-month RR=4.0, 95% CI 2.6 to 6.1). Conclusions: Recent PPNM was associated with incident concurrency. Among young adults, onset of concurrency may be stimulated, relatively quickly, by the PPNM. Programmes which promote relationship communication skills and explicit monogamy expectations may help reduce concurrency.